2004
DOI: 10.1038/sj.leu.2403392
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of immunophenotype, treatment response, and relapse in childhood acute lymphoblastic leukemia using DNA microarrays

Abstract: Gene expression profiling is a promising tool for classification of pediatric acute lymphoblastic leukemia (ALL). We analyzed the gene expression at the time of diagnosis for 45 Danish children with ALL. The prediction of 5-year event-free survival or relapse after treatment by NOPHO-ALL92 or 2000 protocols resulted in a classification accuracy of 78% and a Matthew's correlation coefficient of 0.59 independently of immunophenotypes. The sensitivity and specificity for prediction of relapse were 87% and 69% res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 16 publications
2
32
0
Order By: Relevance
“…by guest www.bloodjournal.org From our data with published data analyzing gene expression profiles of patients with relapsed and successfully treated ALL and treatment-resistant compared with sensitive ALL, respectively. [11][12][13][14][15] A remarkable concordance could be observed comparing our results with the data recently published by Chiaretti et al, 15 who analyzed the expression signatures of adult T-cell ALL. Chiaretti et al 15 identified a set of only 3 genes that were predictive of duration of remission and a list of 30 genes expressed at low levels in treatment-resistant T-cell ALL.…”
Section: Similarities In Resistance-associated Gene Expression Profilsupporting
confidence: 80%
“…by guest www.bloodjournal.org From our data with published data analyzing gene expression profiles of patients with relapsed and successfully treated ALL and treatment-resistant compared with sensitive ALL, respectively. [11][12][13][14][15] A remarkable concordance could be observed comparing our results with the data recently published by Chiaretti et al, 15 who analyzed the expression signatures of adult T-cell ALL. Chiaretti et al 15 identified a set of only 3 genes that were predictive of duration of remission and a list of 30 genes expressed at low levels in treatment-resistant T-cell ALL.…”
Section: Similarities In Resistance-associated Gene Expression Profilsupporting
confidence: 80%
“…This notion is supported by the absence of apoptosis genes among the genes previously associated with treatment response in several studies in diagnostic childhood ALL samples. 42,67,68 In conclusion, this study is the first to describe an association between the differential expression of key apoptosis genes and lineage, genetic subtype, and in vitro drug resistance in children with ALL. In addition, we identified a single gene, BCL2L13, which is related to both L-asparaginase resistance and treatment outcome independent from known prognostic factors in 2 independent cohorts of children with B-lineage ALL.…”
Section: Discussionmentioning
confidence: 76%
“…4,5 Microarray-based gene expression profiling has been used to identify prognosis-associated signatures in childhood acute lymphoblastic leukemia (ALL). [6][7][8][9][10] It has also led to a large set of genes, which are potentially involved in GC response. [11][12][13][14][15] Accordingly, the hypotheses generated to explain the cytotoxic activity of GC are explicitly diverse, reaching from the direct activation of the apoptotic machinery to indirect deregulations of cellular functions, such as nucleotide and protein synthesis, energy metabolism, pH state and redox homeostasis.…”
Section: Introductionmentioning
confidence: 99%